Pemanfaatan Dana Alokasi Khsuus Non Fisik Terhadap Pencapaian Kinerja SPM Kesehatan - Rhomadona, Zully; Nani Sari Murni; arie wahyudi; erma gustina (Avicenna: Jurnal Ilmiah, 2025)
Background: The successful implementation of health sector activities needs to be supported by non-physical Special Allocation Funds (DAK). Non-physical DAK for health is a fund to improve access and quality of health services in the region. Several service targets in North Musi Rawas Regency show that they have not yet reached 100%. This research aims to analyze the use of non-physical DAK on the achievement of health SPM performance at the North Musi Rawas District Health Service. Method: Qualitative research design with a descriptive approach. The research was carried out at 8 Community Health Centers and the North Musi Rawas District Health Service. Information collection was carried out from March to April 2024. Information was collected by in-depth interviews and document review. Result : The research results show that the majority of health workers do not have sufficient competence because they have never attended training. Health workers do not yet have clear duties and functions. All Community Health Centers have a budget for the diabetes mellitus program, but the elderly program budget is only available for 3 Community Health Centers. The available facilities and infrastructure are not yet complete. Health workers do not yet know the policies related to the Diabetes Mellitus (DM) program and the elderly. Program reporting is still manual. Health services for DM sufferers and the elderly have been carried out well. The SPM achievement of DM health services has met the target of 100%, but elderly services have not met the target. The total budget absorption coverage for DM services is 100%, while for the elderly it does not reach 100%. Conclusion : Health service factors, SPM services and non-physical DAK absorption are still not up to standard. Keywords: SPM, Utilization, Funds, Non-Physical DAK, Performance